2014
DOI: 10.1021/am5067139
|View full text |Cite
|
Sign up to set email alerts
|

Osteoconductive Property of a Mechanical Mixture of Octacalcium Phosphate and Amorphous Calcium Phosphate

Abstract: The present study was designed to investigate the extent of osteoconductive property of a mechanical mixture of octacalcium phosphate (OCP) and amorphous calcium phosphate (ACP). OCP was mixed with ACP in granules that had a diameter of 300 and 500 μm, respectively, and at 25, 50, or 75 wt %. The physicochemical characteristics and the osteoconductive properties of the mixtures were compared with OCP alone or ACP alone through implantation into rat critical-sized calvaria defects for up to 12 weeks and simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…The FTIR spectrum of each powder was obtain by FTIR spectroscopy (FT/IR‐4600; JASCO Corporation, Tokyo, Japan) with the sample diluted in KBr over a range of 1400–400 cm −1 with 4 cm −1 resolution. FTIR curve fitting analysis was performed following the method described in our previous study . The intensities of apatitic OH − and nonapatitic HPO 4 2− in FTIR spectra were estimated through curve‐fitting using Spectra Manager Version 2.15.05 (Curve fitting Version 2.06).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FTIR spectrum of each powder was obtain by FTIR spectroscopy (FT/IR‐4600; JASCO Corporation, Tokyo, Japan) with the sample diluted in KBr over a range of 1400–400 cm −1 with 4 cm −1 resolution. FTIR curve fitting analysis was performed following the method described in our previous study . The intensities of apatitic OH − and nonapatitic HPO 4 2− in FTIR spectra were estimated through curve‐fitting using Spectra Manager Version 2.15.05 (Curve fitting Version 2.06).…”
Section: Methodsmentioning
confidence: 99%
“…FTIR curve fitting analysis was performed following the method described in our previous study. 41 The intensities of apatitic OH − and nonapatitic HPO 4 2− in FTIR spectra were estimated through curve-fitting using Spectra Manager Version 2.15.05 (Curve fitting Version 2.06). An IR band ratio between 450 and 700 cm −1 was used according to a method reported by Rey et al 50,51…”
Section: Tartrate-resistant Acid Phosphatase (Trap) Stainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ACP conversion process can serve as a vehicle for delivering calcium and phosphate ions which are necessary for mineralization (Popp et al, ). The literature has demonstrated that the use of ACP has been limited to grafts for bone regeneration in vivo due to its prevailing dissolution‐precipitation (Kobayashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The crystalline phase of OCP differs from the apatite crystalline phase, by a water layer that is located between two layers of apatite [18]. The ACP → OCP → carbonated hydroxyapatite transformation reaction is known to occur in vitro at neutral pH conditions, as well as at physiological pH [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%